The Effect of Work Environment, Competence, and Motivation on Employee’s Performance in Electronic Companies in the Industrial District of Bekasi Regency - Sabil, Sabil; Suhartono, Suhartono; Winarno, Slamet Heri; Putra, Octa Pratama; Widodo, Dwiyatmoko Puji (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2021)
Employee performance is an important element to assess the level of success of the company is running its business. Many factors can affect employee performance, including the environment, work, competence, and employee motivation. This study aims to explore the relationship of influence between these three factors on employee performance. The sample of respondents selected were employees who worked at several electronic companies in the Bekasi Industrial Area, West Java, Indonesia. This study uses structural equation modeling (SEM) and path analysis to test the level of influence of the variables used. The use of 183 employees who come from different characteristics, age, sex, length of work, education, and income are used to test the effect of the work environment, competence and motivation on performance. The results showed that performance was more significantly influenced by the work environment and motivation as intervening, while competence did not significantly influence performance. Motivation also directly influences performance. Companies must be able to create attractive work environments so that employees can be motivated and make optimal use of employee competency planning. This study focuses more on how the work environment, competence, and motivation affect performance both partially and simultaneously.Keywords: Work Environment, Competence, Motivation, Employee’s Performance